The Mechanics Properties of Self-Compacting Concrete Using Red-Tile Waste as Substitution of Fine Aggregates - Octobenita, Crezensia Alfiora Deadema Dias; Lisantono, Ade (MEDIA KOMUNIKASI TEKNIK SIPIL, 2017)
This paper presents the experimental program about the mechanics properties of Self-Compacting Concrete (SCC) using red-tile waste as substitution of fine aggregates. The proportion of red-tile waste substitution was 10 %; 20 %; 30; 40 %; and 50 % of fine aggregates by weight. Viscocrete-10 was used to maintain the workability and flowability of SCC. 72 cylinder specimens with the size of (150×300) mm and 18 beam specimens with the size of (100×100×500) mm were cast and tested in this study. The mechanics properties of SCC that were studied in this research were compressive strength, modulus of elasticity, and modulus of rupture. The compressive strength of SCC was tested at age 7; 14; and 28 days. While the modulus of elasticity and modulus of rupture of SCC were tested only at age 28 days. The result shows that the maximum compressive strength of SCC was obtained using red-tile waste with the proportion of 50 % as substitution of fine aggregates. The compressive strength of SCC using red-tile with the proportion of 50 % at age 7; 14; and 28 days were 64.746 MPa;, 65.564 MPa; and 71.940 MPa, respectively. While the maximum modulus of elasticity and modulus of rupture of SCC were obtained using red-tile with the proportion 50 % at age 28 days, and the modulus elasticity and modulus of rupture were 25863.192 MPa and 7.076 MPa, respectively.